RAINBOW FISH COLOR QUALITY WITH SPIRULINA SUPPLEMENTATION IN FEED - Rahmatia, Firsty; Nainggolan, Armen (Jurnal Ilmiah Universitas Satya Negara Indonesia, 2025)
Rainbowfish originate from Sulawesi and Papua. These rainbow-like colors fish are becoming increasingly popular. Another unique characteristic of this species is its non-aggressive nature, allowing it to be kept with other fish species in the same aquarium. Enhancing the economic value of rainbowfish can be achieved by improving their color quality to make them more visually appealing. One method to achieve uniform bright coloration is through the supplementation of natural pigment sources in their feed. One such natural pigment source is Spirulina platensis, which contains high levels of beta-carotene. Based on this premise, research is necessary to determine the optimal dosage of S. platensis supplementation for enhancing the color quality of rainbowfish, thereby increasing their aesthetic appeal and market value. The tested S. platensis dosages were 0% (Control), 1%, 2%, and 3%, with four replications. The fish were maintained for five weeks, with sampling conducted weekly. Observed parameters included length growth, absolute biomass growth, and color measurement using M-TCF. The results indicated that, statistically, S. platensis supplementation at doses of 1%–3% had no significant effect on the growth of Boesemani Rainbowfish. However, in terms of color enhancement, the best treatment was observed in Treatment B (2% S. platensis dosage).